Theology without Borders : Essays in Honor of Peter C. Phan - Lefebure, Leo D., 1952-; Phan, Peter C., 1943- (Book collections on Project MUSE., 2022)
"Theology without Borders, the title of this volume, evokes the seminal contributions of Peter Phan, a remarkably productive and creative scholar who challenges us to make global humanity the starting point for theological reflection. Over several decades, Phan has persuaded us that the collapse of established, bounded frameworks - especially that of a European Christianity with a monopoly on truth - is not to be feared but celebrated. His prodigious output has contributed to and enriched literatures in ecclesiology, Christology, missiology, patristics, and other fields. This volume brings together the contributions from a number of leading scholars and engages systematically with Phan's ideas across a range of vitally important topics, from global Christianity and migration to religious pluralism, the legacies of the Second Vatican Council, and eschatological controversies. Taken together, the essays provide an overview of Phan's scholarly contributions and a road map for better understanding theology without borders in our contemporary world"--